Application for Thermal Spraying for Rail Vehicles (Current Problems in Rail Vehicles, 2025)
The article deals with the basic types of thermal spraying (including variants of powders, wires). These are defined thermal spraying methods of application and use. For specific applications are the experience with use of the thermal spraying on the components of rail vehicles. At the end is a summary of the suitability of the use of thermal spraying for specific applications.
Keywords: rail vehicle; surface protection; thermal spraying